Beirut Port Blast: Use of Electronic Health Record System During a Mass Casualty Event - Eveline Hitti; Dima Hadid; Miriam Saliba; Zouhair Sadek; Rima Jabbour; Rula Antoun; Mazen El Sayed (Western Journal of Emergency Medicine)
Introduction: Emergency departments (ED) play a central role in defining the effectiveness and quality of the overall hospital’s mass casualty incident (MCI) response. The use of electronic health records (EHR) in hospital settings has been rapidly growing globally. There is, however, a paucity of literature on the use and performance of EHR during MCIs. Methods: In this study we aimed to describe EHR use, as well as the challenges and lessons learnt in response to the 2020 explosion in the Port of Beirut, Lebanon, during which the hospital received over 360 casualties. Results: Information technology support, reducing EHR system restrictions, cross-function training, focus on registration and patient identification, patient flow and tracking, mobility and bedside access, and alternate sites of care are all important areas to focus on during emergency/disaster response planning. Conclusion: Innovative solutions that help address logistical challenges for different aspects of the disaster response are needed.